Frequency decoding of calcium oscillations - Smedler, Erik; Uhlén, Per (Biochimica et biophysica acta, 2014)
Calcium (Ca2+) oscillations are ubiquitous signals present in all cells that provide efficient means to transmit intracellular biological information. Either spontaneously or upon receptor ligand binding, the otherwise stable cytosolic Ca2+ concentration starts to oscillate. The resulting specific oscillatory pattern is interpreted by intracellular downstream effectors that subsequently activate different cellular processes. This signal transduction can occur through frequency modulation (FM) or amplitude modulation (AM), much similar to a radio signal. The decoding of the oscillatory signal is typically performed by enzymes with multiple Ca2+ binding residues that diversely can regulate its total phosphorylation, thereby activating cellular program. To date, NFAT, NF-κB, CaMKII, MAPK and calpain have been reported to have frequency decoding properties. The basic principles and recent discoveries reporting frequency decoding of FM Ca2+ oscillations are reviewed here. A limited number of cellular frequency decoding molecules of Ca2+ oscillations have yet been reported. Interestingly, their responsiveness to Ca2+ oscillatory frequencies shows little overlap, suggesting their specific roles in cells. Frequency modulation of Ca2+ oscillations provides an efficient means to differentiate biological responses in the cell, both in health and in disease. Thus, it is crucial to identify and characterize all cellular frequency decoding molecules to understand how cells control important cell programs. •Ca2+ oscillations provide an efficient means to differentiate cellular responses.•We review the literature on frequency decoding of Ca2+ oscillations.•A limited number of frequency decoding molecules have yet been reported.•Frequency decoding molecules show little overlap, suggesting their specific roles.